Role of personal care products as endocrine disruptors affecting reproductive age women - Nitin Kalsi Rajashekara; Madhumitha Natarajan; Asha Srinivasan; Jovitha Babu; SubbaRao V. Madhunapantula; Bindu Jayshankar; Raghu Nataraj (Frontiers in Reproductive Health)
The impact of endocrine-disrupting chemicals (EDCs) on public health is growing due to their wide-ranging consequence and likelihood of morbidity on human health. Humans are confronted with EDCs through their skin and drinks, as well as by inhaling. EDCs are extensively dispersed in the environment. EDCs have been shown to primarily influence puberty, the reproductive system, embryonic growth, the hypothalamus-pituitary-gonadal axis (HPG) neuroendocrine axis, and gender differentiation in the foetus, despite their capacity to influence a variety of hormone systems. Treatment for afflicted persons will benefit greatly from an understanding of the several ways that modifiable lifestyle circumstances connected to PCPS impede female infertility. The purpose of this review is to raise awareness of the hidden danger that environmental dyes (EDCs) pose to human health, particularly in terms of their detrimental effects on female reproductive health.